Research on mechanical characteristics and key technology of integral intelligent lifting construction of large-span heavy steel box girder - Xiaofeng Liu; Mingliang Li; Zhi Geng; Shuhong Zhu; Wenjie Li; Bin Liang (PLoS ONE, 2025)
This paper aims to address the problems of aerial orientation control and safety in sudden extreme working conditions during the integral intelligent lifting of large-span heavy steel box girder. Based on the project of Xiaotun Bridge of Fuyi Expressway, a new integral lifting system and control method were proposed. To prevent extreme conditions during the lifting process, the mechanical properties of steel box girders in both synchronous and asynchronous integral lifting states were investigated using the finite element method. Moreover, the mechanical properties of the steel box girders during the lifting process were analyzed through on-site monitoring. The results show that an alignment device has been added to the existing synchronous hydraulic lifting system, which achieves precise control of the aerial orientation and stress of each component of the steel box girder through informal lifting, micromotion lifting and other methods. In the synchronous lifting condition, the failure of the lifting point will cause the redistribution of internal forces in the lifting sling, thereby endangering the lifting lugs, but the stress and deformation of the steel box girder change relatively little. In the asynchronized lifting condition, the use of double lifting points may potentially result in overturning and torsion of the girder. However, under the asynchronous lifting within the displacement error limits, the overall mechanical performance of the steel box girder meets the codes. The on-site monitoring results correlate closely with the simulation results for the normal lifting conditions of the steel box girder. The maximum stress and vertical displacement of the steel box girder are approximately 74 MPa and 70 mm, respectively, indicating that the overall girder structure is safe and reliable throughout the entire lifting process.